FHR-NSGA-III: A hybrid many-objective optimizer for intercity multimodal timetable optimization considering travel mode choice - Zhao, Jiandong; Feng, Yingzi; Wu, Jianjun; Gao, Ziyou (Information sciences, 2023)
•We propose a many-objective multimodal timetable optimization model under travel mode choice.•We develop a Fast Hypervolume indicator-based MOEA to improve efficiency for solution seeking.•We provide a hybrid MOEA that combines FH-MOEA with R-NSGA-III to improve solutions’ quality.•We validate our proposed algorithm using intercity networks from three urban agglomerations. Multiple transport modalities often have low frequency and uneven service, which puts customers through an uncomfortable and costly experience due to disorganized transportation. This paper presents a passenger-centric approach for multimodal timetable optimization. We suggest a many-objective mixed programming model that takes the travel mode choice into account. By simulating the utility function of passengers’ perceived travel cost, scheduling measures are developed that also take the time window, capacity, and overtaking into account. Afterwards, by minimizing the number of related solutions, we present a Fast Hypervolume indicator-based Many-objective Evolutionary Algorithm (FH-MOEA), which can swiftly determine the hypervolume contribution of each solution. Furthermore, by merging FH-MOEA with Reference Point Based Multi-Objective Optimization Using Evolutionary Algorithms (R-NSGA-III), we propose the hybrid algorithm FHR-NSGA-III for finding high-quality solutions. Intercity networks between Guangzhou and Qingyuan, Chengdu and Chongqing, and Beijing and Zhangjiakou are the subjects of computational experiments. The results demonstrate the performance of the algorithm in finding high-quality solutions in a computationally efficient manner.